Association of cannabis use during pregnancy with severe acute respiratory syndrome coronavirus 2 infection: a retrospective cohort study. (12th October 2022) - Young‐Wolff, Kelly C.; Ray, G. Thomas; Alexeeff, Stacey E.; Benowitz, Neal; Adams, Sara R.; Does, Monique B.; Goler, Nancy; Ansley, Deborah; Conway, Amy; Avalos, Lyndsay A.
Abstract: Background and Aims: Cannabis use is increasingly common among pregnant individuals and might be a risk factor for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. We aimed to test whether prenatal cannabis use is associated with increased risk of SARS‐CoV‐2 infection during pregnancy. Design: This is a retrospective cohort study. Setting: The study was conducted in California, USA. Participants: A total of 58 114 pregnancies (with outcomes from 5 March 2020 to 30 September 2021) among 57 287 unique pregnant women aged 14–54 years who were screened for prenatal substance use, enrolled in Kaiser Permanente Northern California (KPNC) (a health‐care system) and had not tested positive for COVID‐19 prior to pregnancy onset. Measurements: We utilized data from the KPNC electronic health record. Cannabis use status (current, recently quit and non‐user) was based on universal screenings during prenatal care (including urine toxicology testing and self‐reported use on a self‐administered questionnaire). SARS‐CoV‐2 infection [based on polymerase chain reaction (PCR) tests] was estimated in time‐to‐event analyses using Cox proportional hazard regression models adjusting for covariates. Secondary analyses examined differences in (a) SARS‐CoV‐2 testing rates and (b) SARS‐CoV‐2 infection rates among those tested. Findings: We observed 348 810 person‐months of follow‐up time in our cohort with 41 064 SARS‐CoV‐2 PCR tests and 6% ( n = 2414) of tests being positive. At the start of follow‐up, 7% of pregnant individuals had current use, 12% had recently quit and 81% did not use cannabis. Adjusting for covariates, current use was associated with lower rates of SARS‐CoV‐2 infection [adjusted hazard ratio (aHR) = 0.60, 95% confidence interval (CI) = 0.49–0.74 than non‐use. Those who had recently quit did not differ from non‐cannabis users in infection rates (aHR = 0.96, 95% CI = 0.86–1.08). Sensitivity analyses among patients who received a SARS‐CoV‐2 test also found lower odds of infection associated with current versus no cannabis use (aOR = 0.76, CI = 0.61–0.93). Conclusions: Current cannabis use appears to be associated with a reduced risk of SARS‐CoV‐2 infection among pregnant individuals.